New skin : a novel - Wang, Sarah (Little Brown & Company, 2026)
"At twenty-six, Linli Feng is still trying to escape her mother Fanny's orbit. But after three years of estrangement, just when Linli has been accepted into a prestigious graduate program, she is dragged back by Fanny's latest medical catastrophe and forced to return home. For decades, Fanny has been addicted to plastic surgery, getting bargain procedures in the basements of LA's bootleg beauty industry. Now Fanny's disfigured face is in dangerous revolt, infected and collapsing yet again from black-market injectables. But even as Linli wades through the wreck of family finances and juggles her mother's medical care, Fanny has another secret in store. Fanny has won a spot on America's Beauty Extreme, a reality television competition in which botched plastic surgery addicts compete for reconstructive surgery as riveted audiences tune in. When Linli attempts to rescue Fanny from the sinister subculture that has already claimed her mother's face, she must at last confront the corrosive reality of the American Dream that is at the fraught heart of their relationship.